CONTACTLESS MEASUREMENT OF KEY PARAMETERS OF LIMB VESSELS ON AN OCCLUSAL PLETHYSMOGRAPHY METHOD - V. I. Kuznetsov; S. A. Tarakanov; N. I. Ryzhakov (Бюллетень сибирской медицины)
The purpose of this publication – to familiarize the readers with the newest achievements in the field of vision   machine   technologies   with   regard to the   occlusal   plethysmography.   The   principle   of plethysmograph work is similar to a principle of mechanical occlusal plethysmograph work, with that only a difference that working measuring environment (gas or liquid) is replaced with laser labels, and fixation of change of volume is made by machine vision with the subsequent computer processing. Application of laser technologies of machine vision in future considerably simplified process of diagnostics, will allow to carry out diagnostics repeatedly and under various conditions of, for example, case of external action on the examined finiteness of the of heat, cold, physical exercise, and so, is representative of more and accurate picture of the state of blood vessels in the dynamics.